Basic Science Module as a Resource for Independent Learning for Elementary Teacher Education Students in the Pandemic Covid-19 - Nisa, Ana Fitrotun; Rezkita, Shanta; Cahyo Khosiyono, Banun Havifah; Wijayanti, Astuti; Murniningsih, Murniningsih; Utaminingsih, Retno; Trisniawati, Trisniawati; Sumiyati, Sumiyati (Universitas Pendidikan Ganesha, 2022)
The lack of learning media learning that dares make students find it challenging to learn, especially on the basic concepts of science. An alternative solution for students to learn independently is by developing modules with good module characteristics. This study aims to produce a product in the form of a valid science basic concept module according to the characteristics of a suitable module. This type of research is research and development research with Borg & Gall development procedures. The subjects of this study were three experts in assessment and one evaluation. The population in this study were elementary school teacher study students who took science courses, and the sample of this study was 9. The data collection technique in this study was carried out by distributing questionnaires and product validation sheets. The data analysis technique was carried out using qualitative and quantitative descriptive techniques. The results of this study indicate that the developed science module has clear, independent, independent, adaptive, user-friendly instructions with attractive graphics. The module validation results obtained an average of 103, with a very good category. The results of the response questionnaire distributed to ten students showed that as many as 80% of students added that they were accommodating in independent learning during the pandemic, and as many as 20%. Based on the modules developed were pretty helpful in implementing the learning process during the pandemic. It proves that the module developed is worthy of being used as a source of independent learning during the pandemic.